High-grade myopia and vaginal delivery: A narrative review - Sumual, Vera; Chandra, Angelina Patricia; Sutanto, Reynardi Larope (Science Midwifery, 2024)
This narrative review explores the risks and management considerations of vaginal delivery in individuals with high-grade myopia, a condition associated with potential complications like retinal detachment and choroidal neovascularization. Utilizing 24 references, the review follows a modified rapid literature review model as outlined by Tjoa and Sutanto (2024). Eleven core studies out of an initial 234, including case reports and retrospective studies, were analyzed in the final qualitative assessment. The findings suggest that high-grade myopia, by itself, generally does not require cesarean section (C-section), and vaginal delivery is considered safe for most patients, provided there is regular ophthalmological monitoring throughout pregnancy. There is no strong evidence supporting a universal recommendation for C-section solely due to high myopia, except in the presence of severe complications, such as choroidal neovascularization. The review emphasizes individualized care, with delivery mode decisions tailored to each patient's specific ocular risk factors. Routine C-sections without additional complicating factors are not justified, underscoring the need for regular ophthalmological evaluations to ensure optimal maternal and fetal outcomes. Due to the limitations of existing studies, further in-depth research is recommended to confirm these findings and refine clinical guidelines.